TI_GERICHTE 15.2007.98 vom 12. Februar 2008 , Pignoramento. Accompagnamento forzato dell'escusso per mezzo della polizia - TI Tribunale d'appello (2008)
Pignoramento. Accompagnamento forzato dell'escusso per mezzo della polizia